2016
DOI: 10.1039/c6re00006a
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost instant CO generation at room temperature using formic acid, mesyl chloride and triethylamine

Abstract: A simple and robust method for instant carbon monoxide generation at room temperature using easily accessible standard lab chemicals: formic acid, mesyl chloride and triethylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Carbon monoxide‐releasing molecules (CO‐RMs) are compounds able to release carbon monoxide under specific conditions. Past studies have shown the application of CO‐RMs in medicine as therapeutic agents and in synthetic chemistry as CO trapping‐releasing agents . The synthesis of metal carbonyl complexes, such as rhuthenium‐CO and copper‐CO complexes, and their application as in situ CO‐releasing molecules have rapidly increased .…”
Section: Co‐releasing Molecules (Co‐rms)mentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon monoxide‐releasing molecules (CO‐RMs) are compounds able to release carbon monoxide under specific conditions. Past studies have shown the application of CO‐RMs in medicine as therapeutic agents and in synthetic chemistry as CO trapping‐releasing agents . The synthesis of metal carbonyl complexes, such as rhuthenium‐CO and copper‐CO complexes, and their application as in situ CO‐releasing molecules have rapidly increased .…”
Section: Co‐releasing Molecules (Co‐rms)mentioning
confidence: 99%
“…Past studies have shown the application of CO-RMs in medicine as therapeutic agents 74,75 and in synthetic chemistry as CO trapping-releasing agents. 69,[76][77][78][79][80][81][82][83] The synthesis of metal carbonyl complexes, such as rhuthenium-CO and copper-CO complexes, and their application as in situ CO-releasing molecules have rapidly increased. 69,[84][85][86][87][88] These complexes are able to release CO under physiological conditions 84 or by addition of a competing ligand.…”
Section: Mechanism Of 11 C-carbonylation With [ 11 C]comentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the activity of 12‐G 1 for carbonylative coupling with ex situ generated CO (Scheme B). In a double‐chamber reactor using the technology developed by the group of Skrydstrup, carbon monoxide is produced by decomposition of formic acid in the presence of triethylamine and mesyl chloride according to the procedure described by De Borggraeve et al . The use of such a device enables the handling of this deadly gas in a safe environment.…”
Section: Resultsmentioning
confidence: 99%
“…Veryser et al reported on a related strategy by using mesyl chloride for activating formic acid instead of acetic anhydride. The CO‐liberation was rapid under the developed conditions and could be generated ex situ by using COware for aminocarbonylations and carbonylative cyclizations, respectively. Representative examples of 13 C‐enriched compounds from these studies are depicted in Scheme 29A ( 110 and 111 ).…”
Section: C‐carbonylation Using [13c]comentioning
confidence: 99%